Impaired sensitivity to thyroid hormones and carotid plaque in patients with coronary heart disease: A RCSCD-TCM study in China - Liu, Yijia; Li, Zhu; Yang, Tong; Li, Lin; Yu, Lu; Liu, Fanfan; Ni, Tongyao; Gao, Shan; Li, Chunjie; Yang, Rongrong; Yu, Chunquan (Frontiers in Endocrinology, 2022)
Context Previous studies on the association between thyroid function and carotid plaque have shown contradictory results, which may be attributable to the sensitivity to thyroid hormone indices. This study aimed to analyze the association between thyroid hormone sensitivity and risk of carotid plaque in patients with coronary heart disease (CHD) and further explore this association according to sex, age, smoking, and drinking status. Methods This large-scale, multi-center, retrospective, cross-sectional study included 6679 patients with CHD (age 35–75). Central sensitivity to thyroid hormone was evaluated by the thyroid feedback quantile-based index (TFQI), parametric thyroid feedback quantile-based index (PTFQI), thyroid-stimulating hormone index (TSHI), and thyrotroph thyroxine resistance index (TT4RI). Peripheral sensitivity to thyroid hormone was assessed by free triiodothyronine/free thyroxine (FT3/FT4) ratio. Taking no carotid plaque as a reference, this study used logistic regression to analyze the association between central and peripheral thyroid hormone sensitivity and carotid plaque in patients with CHD. Results Of the 6679 patients with CHD, 4843 (72.50%) had carotid plaque. In the multi-adjusted models, the TFQI (odds ratio [OR]: 1.50; 95% confidence interval [CI]: 1.26–1.78; P < 0.001), PTFQI (OR: 1.76; 95% CI: 1.46–2.12; P < 0.001), TSHI (OR: 1.21; 95% CI: 1.10–1.33; P < 0.001), and TT4RI (OR: 1.00; 95% CI: 1.00–1.01; P = 0.003) were positively associated with the risk of carotid plaque. Compared with that in females and people > 60 years, the OR value for carotid plaque was higher in males and people ≤ 60 years. Similarly, smokers and drinkers had higher OR values for carotid plaque than non-smokers and non-drinkers. Conversely, FT3/FT4 ratio (OR: 0.75; 95% CI: 0.70–0.81; P < 0.001) was negatively associated with carotid plaque, and the OR value for carotid plaque was lower in males, patients ≤ 60 years, smokers, and drinkers. Conclusion This study showed that thyroid hormone sensitivity is significantly associated with carotid plaque in patients with CHD. This association is more significant in males, patients ≤ 60 years, smokers, and drinkers.